Lignin from Tree Barks: Chemical Structure and Valorization. Issue 17 (2nd June 2020) - Neiva, Duarte M.; Rencoret, Jorge; Marques, Gisela; Gutiérrez, Ana; Gominho, Jorge; Pereira, Helena; del Río, José C.
Abstract: Lignins from different tree barks, including Norway spruce ( Picea abies ), eucalyptus ( Eucalyptus globulus ), mimosa ( Acacia dealbata ) and blackwood acacia ( A. melanoxylon ), are thoroughly characterized. The lignin from E. globulus bark is found to be enriched in syringyl (S) units, with lower amounts of guaiacyl (G) and p ‐hydroxyphenyl (H) units (H/G/S ratio of 1:26:73), which produces a lignin that is highly enriched in β‐ether linkages (83 %), whereas those from the two Acacia barks have similar compositions (H/G/S ratio of ≈5:50:45), with a predominance of β‐ethers (73–75 %) and lower amounts of condensed carbon–carbon linkages; the lignin from A. dealbata bark also includes some resorcinol‐related compounds, that appear to be incorporated or intimately associated to the polymer. The lignin from P. abies bark is enriched in G units, with lower amounts of H units (H/G ratio of 14:86); this lignin is thus depleted in β‐O‐4′ alkyl–aryl ether linkages (44 %) and enriched in condensed linkages. Interestingly, this lignin contains large amounts of hydroxystilbene glucosides that seem to be integrally incorporated into the lignin structure. This study indicates that lignins from tree barks can be seen as an interesting source of valuable phenolic compounds. Moreover, this study is useful for tailoring conversion technologies for bark deconstruction and valorization. Abstract : Bark for good : Tree barks are low‐cost and abundant lignocellulosic wastes produced by the wood industries. This study concerns the detailed structural characterization of lignin from different tree barks, which will be of great help for the development of efficient conversion technologies of these materials and will aid in their full valorization. The results indicate that bark lignins are a promising source of valuable phenolic compounds.